Long run determinants of real exchange rate: An econometric analysis from Pakistan - Furrukh Bashir; Adeel Luqman (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2014)
Real Exchange rate is an important player in the growth of the economy as it may lead to higher export by stabilizing currency value at any specific level. This study aims to analyze the determinants of real exchange rate in Pakistan. Time series data is collected from 1972 - 73 to 2012 - 13. Johansen co-integration test and error correction model is utilized for examining long run and short run elasticity's. The study concludes that real exchange rate is depreciated by terms of trade and Price level. While trade restrictions and workers' remittances are exerting negative effect or appreciating real exchange rate of Pakistan in the long run.
Keywords: 330; real exchange rate; price level; terms of trade; trade restrictions; workers' remittances and Johansen co-integration test